The Role of Parents in Supporting Children’s Mental Health - Cendy Luciana Lotulung; Sennyta Andrea Triasta; Juwinner Dedy Kasingku (Universitas Muhammadiyah Enrekang, 2024)
This study is descriptive-qualitative research using a library research approach, focusing on the role of parents in supporting children's mental health. Children's mental health is something parents need to pay attention to. Parents have a responsibility as the primary educators in supporting various aspects of their children's lives, especially in maintaining their mental health to avoid issues with their mental development. This study also aims to understand the types and symptoms of mental health issues and the factors that can influence them. The results show that parents play a crucial role in supporting children's mental health to prevent issues that could affect their lives and futures. Parents need to create a safe and supportive environment, attend to their children's emotional needs, and facilitate open communication. By doing so, children can develop well and have optimal mental health, which is essential for their future success.